Testis-Specific Bb8 Is Essential in the Development of Spermatid Mitochondria. - Vedelek, V.; Laurinyecz, B.; Kovács, A.L.; Juhász, G.; Sinka, R. (PLoS ONE, 2016)
Mitochondria are essential organelles of developing spermatids in Drosophila, which undergo dramatic changes in size and shape after meiotic division, where mitochondria localized in the cytoplasm, migrate near the nucleus, aggregate, fuse and create the Nebenkern. During spermatid elongation the two similar mitochondrial derivatives of the Nebenkern start to elongate parallel to the axoneme. One of the elongated mitochondrial derivatives starts to lose volume and becomes the minor mitochondrial derivative, while the other one accumulates paracrystalline and becomes the major mitochondrial derivative. Proteins and intracellular environment that are responsible for cyst elongation and paracrystalline formation in the major mitochondrial derivative need to be identified. In this work we investigate the function of the testis specific big bubble 8 (bb8) gene during spermatogenesis. We show that a Minos element insertion in bb8 gene, a predicted glutamate dehydrogenase, causes recessive male sterility. We demonstrate bb8 mRNA enrichment in spermatids and the mitochondrial localisation of Bb8 protein during spermatogenesis. We report that megamitochondria develop in the homozygous mutant testes, in elongating spermatids. Ultrastructural analysis of the cross section of elongated spermatids shows enlarged mitochondria and the production of paracrystalline in both major and minor mitochondrial derivatives. Our results suggest that the Bb8 protein and presumably glutamate metabolism has a crucial role in the normal development and establishment of the identity of the mitochondrial derivatives during spermatid elongation.